Emerging Relationships between Exercise, Sensory Nerves, and Neuropathic Pain - Cooper, Michael A.; Kluding, Patricia M.; Wright, Douglas E. (Frontiers in Neuroscience, 2016)
The utilization of physical activity as a therapeutic tool is rapidly growing in the medical community and the role exercise may offer in the alleviation of painful disease states is an emerging research area. The development of neuropathic pain is a complex mechanism, which clinicians and researchers are continually working to better understand. The limited therapies available for alleviation of these pain states are still focused on pain abatement and as opposed to treating underlying mechanisms. The continued research into exercise and pain may address these underlying mechanisms, but the mechanisms which exercise acts through are still poorly understood. The objective of this review is to provide an overview of how the peripheral nervous system responds to exercise, the relationship of inflammation and exercise, and experimental and clinical use of exercise to treat pain. Although pain is associated with many conditions, this review highlights pain associated with diabetes as well as experimental studies on nerve damages-associated pain. Because of the global effects of exercise across multiple organ systems, exercise intervention can address multiple problems across the entire nervous system through a single intervention. This is a double-edged sword however, as the global interactions of exercise also require in depth investigations to include and identify the many changes that can occur after physical activity. A continued investment into research is necessary to advance the adoption of physical activity as a beneficial remedy for neuropathic pain. The following highlights our current understanding of how exercise alters pain, the varied pain models used to explore exercise intervention, and the molecular pathways leading to the physiological and pathological changes following exercise intervention.